Reintroducing a keystone bioturbator can facilitate microbial bioremediation in urban polluted sediments. (1st May 2023) - Bugnot, A.B.; Dafforn, K.A.; Erickson, K.; McGrath, A.; O'Connor, W.A.; Gribben, P.E.
Abstract: Anthropogenic environmental stressors have significantly reduced biodiversity and the capacity of remnant natural habitats to deliver ecosystem functions and services in urban areas. To mitigate these impacts and recover biodiversity and function, ecological restoration strategies are needed. While habitat restoration is proliferating in rural and peri-urban areas, strategies purposely designed to succeed under the environmental, social and political pressures of urban areas are lacking. Here, we propose that ecosystem health in marine urban areas can be improved by restoring biodiversity to the most dominant habitat, unvegetated sediments. We reintroduced a native ecosystem engineer, the sediment bioturbating worm Diopatra aciculata, and assessed their effects on microbial biodiversity and function. Results showed that worms can affect the diversity of microbes, but effects varied between locations. Worms caused shifts in microbial community composition and function at all locations. Specifically, the abundance of microbes capable of chlorophyll production (i.e. benthic microalgae) increased and the abundance of microbes capable of methane production decreased. Moreover, worms increased the abundances of microbes capable of denitrification in the site with lowest sediment oxygenation. Worms also affected microbes capable of degrading the polycyclic aromatic hydrocarbon toluene, although the direction of that effect was site-specific. This study provides evidence that a simple intervention such as the reintroduction of a single species can enhance sediment functions important for the amelioration of contamination and eutrophication, although further studies are needed to understand the variation in outcomes between sites. Nevertheless, restoration strategies targeting unvegetated sediments provide an opportunity to combat anthropogenic stressors in urban ecosystems and may be used for precondition before more traditional forms of habitat restoration such as seagrass, mangrove and shellfish restoration. Graphical abstract: Image 1 Highlights: Sediment infauna can be restored to drive beneficial microbial functions. Infauna changed microbial communities and increased benthic microalgae. Microbes capable of methanogenesis were less abundant with infauna. Effects on microbial capacity to degrade organic pollutants varied between sites. Interactions between sediment infauna and microbes can enhance bioremediation.